2019
DOI: 10.1136/wjps-2019-000038
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment for Wilms tumor: COG and SIOP standards

Abstract: BackgroundWilms tumor (WT) is the most common renal malignant tumor in children. It occurs primarily at preschool age. The purpose of this review is to present current standards of diagnosis and treatment of WT around the world.Data sourcesAll the recent literature on diagnosis and treatment of WT were searched and reviewed.ResultsMost cases with WT are sporadic. The current survival in patients with WT is high (90%). Involvement of mutidisciplinary collaborative groups in the diagnosis and treatment of WT. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 21 publications
0
54
0
1
Order By: Relevance
“…The cytomorphology of anaplastic WT is well described 13 . The presence of any anaplasia on fine needle aspiration or core biopsy specimen would be considered as diffuse anaplasia as per COG guidelines 18 . Loke et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytomorphology of anaplastic WT is well described 13 . The presence of any anaplasia on fine needle aspiration or core biopsy specimen would be considered as diffuse anaplasia as per COG guidelines 18 . Loke et al.…”
Section: Discussionmentioning
confidence: 99%
“…13 The presence of any anaplasia on fine needle aspiration or core biopsy specimen would be considered as diffuse anaplasia as per COG guidelines. 18 Loke et al in their comparative analysis of Asian versus non-Asian WT reported a frequency of unfavourable histology of just 4.1% in Asians as compared to 25% in non-Asians. 19 Cell blocks from FNA samples act as microbiopsies, and hence an FNA sample was designated as FNABC.…”
Section: Cell Blocks In Wtmentioning
confidence: 98%
“…Preoperative chemotherapy by the COG has four regimes ( Table 6 ). The agents for chemotherapy commonly are doxorubicin plus dactinomycin and vincristine; if with anaplastic histology, chemotherapy then includes regimen I ( Table 6 ) [ 34 ].…”
Section: Recent Advances In Wt Predispositionmentioning
confidence: 99%
“… SIOP Studies: The SIOP guideline recommends preoperative chemotherapy for all patients after diagnosis. For patients with unilateral localized tumor, 4-week pretreatment with vincristine (weekly) and dactinomycin (biweekly) is given; for patients with bilateral tumors, vincristine– dactinomycin for no longer than 9–12 weeks is recommended (doxorubicin is added for reinforcement in some patients); for patients with metastasis, a regimen including 6 weeks of vincristine–dactinomycin (like above) and doxorubicine on weeks 1 and 5 is given [ 34 ]. …”
Section: Recent Advances In Wt Predispositionmentioning
confidence: 99%
See 1 more Smart Citation